Minimal incision cochlear implantation: is it the future - Saroch, Munish; Saini, Amit; Gargi, Gaveshna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The objective of the study was to compare the incision size, operative time and complications in minimal incision cochlear implantation (MICI) and standard incision cochlear implantation (SICI). Methods: Patients who underwent cochlear implant surgery from August 2015 to August 2017. Patients in the MICI group underwent surgery with 2 cm post aural incision whereas patients in SICI group underwent surgery with inverted J incision. Results: A total of eight patients who underwent cochlear implantation during study period were divided into SICI and MICI group of four patients each. The mean size of incision in SICI group was 7.62cm (SD 0.47) and in MICI group was 2 cm. The mean operative time in SICI group was 211.25 minutes (SD 8.53) and in MICI group was 247.5 minutes (SD 11.9). One patient (25%) in SICI group had flap necrosis where as MICI group had none. Conclusions: The MICI can be performed with a small incision of 2 cm. It causes less trauma to the flap with very less incidence of flap necrosis. Technique can be mastered by surgeon with less experience in Cochlear Implant surgery. Other complications are comparable to SICI though operating time is more initially. This is a small study which indicates that Minimal Incision cochlear Implantation is less traumatic and has a more favourable cosmetic outcome with benefits comparable to that of standard technique.